Cultural context and cross-country behavioral differences in group decision-making. Issue 2 (2nd April 2020) - Horak, Sven; Arya, Bindu
Abstract: This study tests the influence of culture on group decision-making behavior among respondents in Korea and Germany. For our field experiment we are using an ultimatum game design, played among participants in Korea and in a benchmark experiment in Germany. We find evidence that taking the mosaic view of culture and making subjects aware of shared affective ties, based on age, educational-institution and regional origin, leads to differences in economic decisions, contrary to what neoclassical economic theory would suggest. Our results indicate that awareness of common group membership in some cultural contexts orients decision-makers toward upholding social norms that induces a greater preference for more selfless, in-group interested decisions, while anonymity makes personal identity salient and promotes more self-interested economic decisions. These effects are more pronounced in Korean participants compared with German participants.